2022
DOI: 10.1371/journal.pone.0271221
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and determinants of HIV prevalence among adults in urban Ethiopia: Findings from the Ethiopia Population-based HIV Impact Assessment Survey (2017–2018)

Abstract: The design and evaluation of national HIV programs often rely on aggregated national data, which may obscure localized HIV epidemics. In Ethiopia, even though the national adult HIV prevalence has decreased, little information is available about local areas and subpopulations. To inform HIV prevention efforts for specific populations, we identified geographic locations and drivers of HIV transmission. We used data from adults aged 15–64 years who participated in the Ethiopian Population-based HIV Impact Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Several studies conducted in Ethiopia [ 11 , 12 , 14 , 15 , 16 , 18 ] and in other countries, including Nigeria [ 22 , 23 ], China [ 21 ], and South Africa [ 24 ], revealed a strong tendency toward the spatial clustering of TB at different geographic scales. Similarly, a number of studies showed the spatial clustering of HIV at different scales [ 19 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies conducted in Ethiopia [ 11 , 12 , 14 , 15 , 16 , 18 ] and in other countries, including Nigeria [ 22 , 23 ], China [ 21 ], and South Africa [ 24 ], revealed a strong tendency toward the spatial clustering of TB at different geographic scales. Similarly, a number of studies showed the spatial clustering of HIV at different scales [ 19 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spatial analysis of a disease helps to understand the spatial epidemiology of the disease occurrence (incidence) at different administrative levels [ 10 ]. There are several studies in Ethiopia that have investigated the spatial clustering of TB and HIV separately at various levels [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Studies in other countries also reported spatial clustering of tuberculosis, e.g., in Brazil [ 20 ], China [ 21 ], Nigeria [ 22 , 23 ] and in South Africa [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, in the current study, widowhood was related to a higher likelihood of positive HIV-RDT, especially in men. Along with this, widowers (male widows) in Ethiopia and Zimbabwe are reported as the population with high HIV prevalence since they may engage in hazardous sexual activities with a high rate of partner change (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the long-term trends and spatial distribution of HIV/AIDS prevalence among older adults in Eastern China have not been adequately assessed. The design and evaluation of national HIV/AIDS planning often rely on comprehensive national data, which can mask local HIV/AIDS epidemics [ 10 ]. To better control the HIV/AIDS epidemic, a more comprehensive and detailed analysis of HIV/AIDS among older adults in Eastern China is needed.…”
Section: Introductionmentioning
confidence: 99%